The Efforts to Increase Student Learning Motivation Through a Culturally Responsive Teaching (CRT) Approach to Biodiversity Material - Nurulaini, Putri Nida; Permana, Irvan; Holiyani, Irna (Jurnal Report of Biological Education, 2023)
Background: Motivation is a series of efforts to achieve certain conditions, so that someone is want to do it. It is known that students' learning motivation is still low, indicated by students' behavior that is less active in learning. The aim of this research is an effort to increase students' learning motivation through a Culturally Responsive Teaching approach to Biodiversity material. Methods: This research is Classroom Action Research (PTK), conducted at SMAN 9 Bogor City with research subjects namely class X.7 students, totaling 36 students. The research time for this classroom action was carried out during July-August 2023. This research was carried out collaboratively based on lesson study. In practice, this classroom action research is carried out through stages in cycles, with a series in each cycle, namely the planning, implementation, observation and reflection stages. Results: In cycles 1 and II overall there was a significant increase because all students were motivated so that no students had sufficient motivation in cycles I and II. In cycle I, 17 people (47%) stated that they were motivated and had high motivation and 19 people (53%) stated that they were motivated and had very high motivation in participating in learning activities using the Culturally Responsive Teaching approach. In cycle II students who are motivated and have very high motivation have increased to 29 students (81%) and students who have high motivation are 7 people (19%) students total. Conclusion: ased on the results of distributing motivation questionnaires, it can be seen that there is an increase in students' learning motivation in each cycle. Keywords : Culturally Responsive Teaching; Biodiversity; Motivation to learn